Liquid-phase growth and optoelectronic properties of two-dimensional hybrid perovskites CH3NH3PbX3 (X = Cl, Br, I). Issue 2 (17th December 2019) - Bai, Yu; Zhang, Haixin; Zhang, Mingjing; Wang, Di; Zeng, Hui; Zhao, Jun; Xue, Hao; Wu, Guozheng; Su, Jing; Xie, Ying; Zhang, Yuxia; Jing, Hao; et al.
Abstract : A bottom-up route to fabricate molecularly thin CH3 NH3 PbX3 (X = Cl, Br, I) perovskite 2D crystals has been discovered and is very promising for superior new optoelectronic devices. Abstract : The hybrid perovskite CH3 NH3 PbX3 (X = Cl, Br, I) is a promising material for developing novel optoelectronic devices. Due to its intrinsic non-layered crystal structure, it remains challenging to synthesize two-dimensional (2D) single-crystalline CH3 NH3 PbX3 with nanoscale thickness. Here, we report a bottom-up approach to fabricate large CH3 NH3 PbX3 2D crystals via liquid-phase growth on a mica substrate. The strong potassium-halogen interactions at the perovskite/mica interface decrease the interface energy, driving the striking in-plane growth of the perovskite. The grown 2D CH3 NH3 PbBr3 crystal was characterized as 8 nm in thickness and hundreds of micrometers in lateral size. Weak exciton binding energy was crucial for improving the photoelectric performance of 2D CH3 NH3 PbBr3 . A visible-light photodetector with a metal/insulator/perovskite configuration was finally achieved with a photoresponsivity of 126 A W −1 and a bandwidth exceeding 80 kHz. Our work proves that the liquid-phase growth on mica is a controllable method to grow 2D hybrid CH3 NH3 PbX3 perovskites, which can facilitate both device applications and fundamental investigations.